The Development and Precision of a Custom-Made Skitester - Lemmettylä, Teemu; Heikkinen, Teemu; Ohtonen, Olli; Lindinger, Stefan; Linnamo, Vesa (Frontiers in Mechanical Engineering, 2021)
In the sport of cross-country skiing, equipment has a direct influence on results. Ski teams do extensive testing of different ski base grinds and products on a yearly basis. To achieve reliable results, the quality of methods used for testing skis needs to be taken in to account in addition to other factors like test persons differences and change in weather condition are increasing the uncertainty of the results. The aim of this study was to introduce a custom-made skitester, that was developed for ski testing on real snow in laboratory conditions and to evaluate its precision. The current skitester is capable of glide testing of classic and skate skis as well as kick simulation for testing grip waxes. In the present study, glide testing precision was completed in three different conditions. Effect of velocity and pressure were evaluated in three different settings. During kick simulation, precision was determined in one condition. For glide testing, the precision of the measurement unit can distinguish the differences between skis at with relative variation (0.6 %-1.1 %) but track preparation process needs to be re-approached. For kick simulation, precision of the measurement unit was slightly higher (2.5 %), and track preparation process caused less variation. The skitester is capable of distinguishing the differences between both skate and classic cross-country skis with certain limitations.